Tracking of the GMPP for a Photovoltaic generator using Model- Free Control and Particle Swarm Optimisation - MENNAD MERIEM; ABOUCHABANA Nabil (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DÉPARTEMENT D'ÉLECTRONIQUE, 2024)
This project investigates advanced Maximum Power Point This thesis investigates advanced MPPT techniques and control strategies for enhancing PV system performance under partial shading conditions. It compares Perturb and Observe (P&O) with Particle Swarm Optimization (PSO), integrating Proportional-Integral (PI) controllers and Model-Free Control (MFC). Through simulations, the study assesses the accuracy and stability of these methods. R´esum´e Ce projet examine les techniques avanc´ees de suivi du Point de Puissance Maximale Global (GMPPT) et les strat´egies de contrˆole pour am´eliorer les performances des syst`emes photovolta¨ıques sous conditions de ombrage partiel. Il compare les techniques Perturb and Observe (P&O) avec l’optimisation par essaim de particules (PSO), int´egrant des r´egulateurs proportionnels-int´egrateurs (PI) et le contrˆole sans mod`ele (MFC). A travers des simulations, l’´etude ´evalue la pr´ecision et la stabilit´e de ces ` m´ethodes.
Automation & Industrial Computing